Graphite negative electrode material and preparation method thereof, negative electrode and lithium ion battery

By densifying natural graphite and coating it with a graphene layer, the problem of particle cracking caused by uneven stress in natural graphite in lithium-ion batteries is solved, improving the specific capacity and cycle life of the material, making it suitable for industrial production.

CN119381429APending Publication Date: 2025-01-28中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423309.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Natural graphite, as a negative electrode material for lithium-ion batteries, is prone to surface cracking due to uneven stress during charging and discharging, and has a poor cycle life. Existing technologies make it difficult to improve its specific capacity and cycle performance at the same time.

Method used

By mixing natural graphite with asphalt and densifying it, filling the internal pores and coating it with a graphene layer, a graphite anode material with internal densification and surface graphene coating is formed. Combining the high Li+ transport rate and lithium storage capacity of graphene, the electrochemical performance of the material is improved.

Benefits of technology

It achieves improved specific capacity and initial efficiency while extending cycle life, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381429A_ABST
    Figure CN119381429A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a graphite negative electrode material and a preparation method thereof, a negative electrode and a lithium ion battery. The graphite negative electrode material comprises a densified natural graphite material and a graphene layer coated on the surface of the densified natural graphite material. Natural graphite and asphalt are mixed and then subjected to densification treatment, natural graphite with pores filled with the asphalt inside and the surface coated with the asphalt is obtained, a natural graphite material with densified internal pores is obtained after graphitization treatment, and then the densified natural graphite material is subjected to graphene surface coating, so that the composite material is obtained. And finally obtaining the graphite negative electrode material which is internally densified and coated with graphene on the surface. The graphite negative electrode material prepared by the method has high specific capacity and first efficiency, and also has excellent rate and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a graphite negative electrode material and a preparation method thereof, a negative electrode and a lithium ion battery. Background Art

[0002] Since the 21st century, traditional fossil energy has gradually become scarce, and the burning of fossil fuels has also led to increased environmental pollution. Therefore, new green and clean energy has begun to come into people's attention. Since the successful commercialization of lithium-ion batteries in the 1990s, they have been widely used in consumer electronics and electric vehicles due to their high energy density, high power performance, long cycle life, and environmental friendliness. In recent years, with the continuous development of markets such as consumer electronics and electric vehicles, the demand for higher energy density, higher fast charging performance and longer cycle life of lithium-ion batteries has become more urgent.

[0003] As an important component of negative electrode materials for lithium-ion batteries, natural graphite has the advantages of high specific capacity, good processability, and low price. However, due to the pores inside the particles, natural graphite is prone to uneven stress during the charge and discharge process, resulting in cracks on the particle surface, and the electrolyte enters the particles to form a new SE I film, causing Li + Excessive consumption and poor cycle life. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a graphite negative electrode material and a preparation method thereof, a negative electrode and a lithium ion battery.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A graphite negative electrode material comprises a densified natural graphite material and a graphene layer coated on the surface of the densified natural graphite material.

[0007] The densified natural graphite material is prepared by the following method: 1) mixing natural graphite microspheres with asphalt and then pressurizing and heating them for densification treatment to obtain natural graphite filled with asphalt inside and coated with asphalt on the surface; 2) continuing high-temperature graphitization treatment to obtain the densified natural graphite material.

[0008] Step 1) The mass ratio of natural graphite microspheres to asphalt is 100:(8-20); preferably 100:15;

[0009] Preferably, the natural graphite microsphere D 50 5 to 25 μm; the graphite negative electrode material D 50 5 to 25 μm; preferably 16.8 to 18 μm;

[0010] Preferably, the asphalt is any one or more of petroleum asphalt and coal tar asphalt, the softening point of the asphalt is 60-90°C, and the quinoline insoluble content is ≤1%;

[0011] Preferably, natural graphite microspheres and asphalt are mixed in a mixer at a speed of

[0012] 150~300r / min, time is 60~120min.

[0013] The specific parameters of the densification treatment by pressurizing and heating in step 1) are: the pressurizing pressure is 100-150Mpa, the temperature is 250-350°C, and the treatment time is 60-120min.

[0014] In step 2), the graphitization treatment temperature is 2500-3000° C. and the time is 2-10 hours.

[0015] The present invention also includes a method for preparing the graphite negative electrode material, comprising the following steps: 1) preparing a densified natural graphite material; 2) adding the densified natural graphite material and a binder into a graphene solution to mix and form a slurry, and then performing a fusion reaction to obtain a graphene-natural graphite fusion product; 3) carbonizing the graphene-natural graphite fusion product to obtain a graphite negative electrode material.

[0016] In step 2), the mass ratio of the densified natural graphite material, graphene, and binder is 100:(5-20):(1-10); preferably 100:(6-8):2;

[0017] The mass concentration of the graphene solution is (1-5)%; the solvent of the graphene solution is one or a mixture of two or more of water, methanol, ethanol, and N-methylpyrrolidone;

[0018] The binder is one or a mixture of two or more of sodium hydroxymethyl cellulose, stearic acid, polyvinyl alcohol, phenolic resin, epoxy resin, glucose, starch, and asphalt;

[0019] The number of graphene layers is 1 to 5, and the diameter of the sheet is 5 to 25 μm.

[0020] In step 2), the fusion reaction is carried out in a fusion machine at a speed of 50 to 200 r / min for 5 to 30 min;

[0021] Preferably, step 3) carbonization treatment is carried out in an inert gas at a temperature of 800-1500° C., a heating rate of 5-10° C. / min, and a time of 1-10 h; the inert gas is one or more of nitrogen or argon.

[0022] The present invention also includes a negative electrode, including the graphite negative electrode material, a negative electrode binder and a negative electrode conductive agent; preferably, the negative electrode binder is a mixture of sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, and the mass ratio of the two is 1:1.5; preferably, the negative electrode conductive agent is conductive carbon black SP.

[0023] The present invention also includes a lithium ion battery, comprising the negative electrode, the positive electrode, the separator and the electrolyte.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention obtains natural graphite with asphalt mixed and densified to obtain natural graphite with asphalt filling pores and asphalt coating on the surface, obtains natural graphite material with densified internal pores after graphitization, and then coats the densified natural graphite material with graphene to finally obtain a graphite negative electrode material with densified internal pores and graphene coating on the surface. The graphite negative electrode material obtained by this method has high specific capacity and first efficiency, and excellent rate and cycle performance.

[0026] (2) Asphalt filling greatly reduces the internal pores of natural graphite particles, alleviates the particle cracking caused by uneven stress during the cycle, and greatly improves the cycle life, but the specific capacity is low. After adding graphene surface coating, the interlayer spacing of the graphene coating layer is larger, which can increase the Li + The transmission rate is increased, the impedance is reduced, and the rate performance is improved; at the same time, because graphene has two lithium storage mechanisms, namely, interlayer lithium storage and defect adsorption lithium storage, it can accommodate more Li than the graphite structure. + , which greatly improves the specific capacity of the material, but too much graphene interface will lead to a decrease in the initial efficiency of the material. Because the internal pores of natural graphite are filled, the Li + The loss can improve the material's first efficiency, solving the problem of reduced first efficiency caused by graphene coating, so that the material has high specific capacity and high first efficiency. The asphalt internal filling and graphene surface coating work together, and the two complement each other, significantly improving the material's specific energy and greatly improving its cycle life.

[0027] (3) The graphite negative electrode material prepared by the method of the present invention has a first discharge specific capacity of ≥375 mAh / g, which exceeds the upper limit of the ideal graphite capacity (372 mAh / g), a first coulombic efficiency of ≥93%, and a capacity retention rate of ≥85% after 1000 cycles at room temperature and 1C. At the same time, the preparation method of the present invention has low cost and simple process, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1This is a scanning electron microscope image of the cross section of the graphite negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0030] Example 1

[0031] A method for preparing a graphite negative electrode material comprises the following steps:

[0032] 1) Preparing densified natural graphite material;

[0033] 1.1) 100 g of natural graphite microspheres with a D50 of 15 μm and 8 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and mixed for 90 min to obtain a mixture;

[0034] The mixture is placed in a hot isostatic press, heated to 250°C under a pressure of 100 MPa, kept at this temperature for 60 minutes, and then cooled to room temperature, broken up, and sieved to obtain natural graphite filled inside and coated with asphalt on the surface;

[0035] 1.2) placing the natural graphite filled with asphalt and coated with asphalt in step 1.1) in a graphitization furnace, treating at 2800° C. for 4 h, and obtaining densified natural graphite after cooling;

[0036] 2) adding the densified natural graphite material and the binder into the graphene solution to mix and prepare a slurry for fusion reaction to obtain a graphene-natural graphite fusion;

[0037] 6 g of graphene powder was dissolved in 120 ml of ethanol and stirred to obtain a graphene solution; 100 g of densified natural graphite obtained in 1.2) and 2 g of a binder, stearic acid, were added to the graphene solution and stirred to obtain a mixed slurry of natural graphite and graphene;

[0038] The mixed slurry is placed in a fusion machine at a speed of 100 r / min for 10 min to perform a fusion reaction to obtain a graphene-natural graphite fusion product;

[0039] 3) placing the fusion product of step 2) in a tube furnace under a nitrogen atmosphere, heating the temperature to 1000° C. at a rate of 5° C. / min for 2 h to obtain a graphite negative electrode material ( Figure 1 shown).

[0040] Example 2

[0041] A method for preparing a graphite negative electrode material comprises the following steps:

[0042] 1) Preparing densified natural graphite material;

[0043] 1.1) 100 g of natural graphite microspheres with a D50 of 15 μm and 11 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and mixed for 90 min to obtain a mixture;

[0044] The mixture is placed in a hot isostatic press, heated to 250°C under a pressure of 100 MPa, kept at this temperature for 60 minutes, and then cooled to room temperature, broken up, and sieved to obtain natural graphite filled inside and coated with asphalt on the surface;

[0045] 1.2) placing the natural graphite obtained in step 1.1) with internal filling and surface coating of asphalt in a graphitization furnace, treating at 2800° C. for 4 h, and obtaining densified natural graphite after cooling;

[0046] 2) adding the densified natural graphite material and the binder into the graphene solution to mix and prepare a slurry for fusion reaction to obtain a graphene-natural graphite fusion;

[0047] 6 g of graphene powder was dissolved in 120 ml of ethanol and stirred to obtain a graphene solution; 100 g of densified natural graphite obtained in 1.2) and 2 g of a binder, stearic acid, were added to the graphene solution and stirred to obtain a mixed slurry of natural graphite and graphene;

[0048] The mixed slurry is placed in a fusion machine at a speed of 100 r / min for 10 min to perform a fusion reaction to obtain a graphene-natural graphite fusion product;

[0049] 3) placing the fusion product of step 2) in a tubular furnace under a nitrogen atmosphere, heating the temperature to 1000° C. at a rate of 5° C. / min for 2 h to obtain a graphite negative electrode material.

[0050] Example 3

[0051] A method for preparing a graphite negative electrode material comprises the following steps:

[0052] 1) Preparing densified natural graphite material;

[0053] 1.1) 100 g of natural graphite microspheres with a D50 of 15 μm and 15 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and mixed for 90 min to obtain a mixture;

[0054] The mixture is placed in a hot isostatic press, heated to 250°C under a pressure of 100 MPa, kept at this temperature for 60 minutes, and then cooled to room temperature, broken up, and sieved to obtain natural graphite filled inside and coated with asphalt on the surface;

[0055] 1.2) placing the natural graphite obtained in step 1.1) with internal filling and surface coating of asphalt in a graphitization furnace, treating at 2800° C. for 4 h, and obtaining densified natural graphite after cooling;

[0056] 2) adding the densified natural graphite material and the binder into the graphene solution to mix and prepare a slurry for fusion reaction to obtain a graphene-natural graphite fusion;

[0057] 6 g of graphene powder was dissolved in 120 ml of ethanol and stirred to obtain a graphene solution; 100 g of densified natural graphite obtained in 1.2) and 2 g of a binder, stearic acid, were added to the graphene solution and stirred to obtain a mixed slurry of natural graphite and graphene;

[0058] The mixed slurry is placed in a fusion machine at a speed of 100 r / min for 10 min to perform a fusion reaction to obtain a graphene-natural graphite fusion product;

[0059] 3) placing the fusion product of step 2) in a tubular furnace under a nitrogen atmosphere, heating the temperature to 1000° C. at a rate of 5° C. / min for 2 h to obtain a graphite negative electrode material.

[0060] Example 4

[0061] A method for preparing a graphite negative electrode material comprises the following steps:

[0062] 1) Preparing densified natural graphite material;

[0063] 1.1) 100 g of natural graphite microspheres with a D50 of 15 μm and 15 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and mixed for 90 min to obtain a mixture;

[0064] The mixture is placed in a hot isostatic press, heated to 250°C under a pressure of 100 MPa, kept at this temperature for 60 minutes, and then cooled to room temperature, broken up, and sieved to obtain natural graphite filled inside and coated with asphalt on the surface;

[0065] 1.2) placing the natural graphite obtained in step 1.1) with internal filling and surface coating of asphalt in a graphitization furnace, treating at 2800° C. for 4 h, and obtaining densified natural graphite after cooling;

[0066] 2) adding the densified natural graphite material and the binder into the graphene solution to mix and prepare a slurry for fusion reaction to obtain a graphene-natural graphite fusion;

[0067] 8 g of graphene powder was dissolved in 120 ml of ethanol and stirred to obtain a graphene solution; 100 g of densified natural graphite obtained in 1.2) and 2 g of a binder, stearic acid, were added to the graphene solution and stirred to obtain a mixed slurry of natural graphite and graphene;

[0068] The mixed slurry is placed in a fusion machine at a speed of 100 r / min for 10 min to perform a fusion reaction to obtain a graphene-natural graphite fusion product;

[0069] 3) placing the fusion product of step 2) in a tubular furnace under a nitrogen atmosphere, heating the temperature to 1000° C. at a rate of 5° C. / min for 2 h to obtain a graphite negative electrode material.

[0070] Example 5

[0071] A method for preparing a graphite negative electrode material comprises the following steps:

[0072] 1) Preparing densified natural graphite material;

[0073] 1.1) 100 g of natural graphite microspheres with a D50 of 15 μm and 15 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and mixed for 90 min to obtain a mixture;

[0074] The mixture is placed in a hot isostatic press, heated to 250°C under a pressure of 100 MPa, kept at this temperature for 60 minutes, and then cooled to room temperature, broken up, and sieved to obtain natural graphite filled inside and coated with asphalt on the surface;

[0075] 1.2) placing the natural graphite filled with asphalt and coated with asphalt in step 1.1) in a graphitization furnace, treating at 2800° C. for 4 h, and obtaining densified natural graphite after cooling;

[0076] 2) adding the densified natural graphite material and the binder into the graphene solution to mix and prepare a slurry for fusion reaction to obtain a graphene-natural graphite fusion;

[0077] 10 g of graphene powder was dissolved in 120 ml of ethanol and stirred to obtain a graphene solution; 100 g of densified natural graphite obtained in 1.2) and 2 g of a binder, stearic acid, were added to the graphene solution and stirred to obtain a mixed slurry of natural graphite and graphene;

[0078] The mixed slurry is placed in a fusion machine at a speed of 100 r / min for 10 min to perform a fusion reaction to obtain a graphene-natural graphite fusion product;

[0079] 3) placing the fusion product of step 2) in a tubular furnace under a nitrogen atmosphere, heating the temperature to 1000° C. at a rate of 5° C. / min for 2 h to obtain a graphite negative electrode material.

[0080] Comparative Example 1:

[0081] A method for preparing a graphite negative electrode material comprises the following steps:

[0082] (1) 100 g of natural graphite microspheres with a D50 of 15 μm and 11 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and the mixture was mixed for 90 min to obtain a mixture;

[0083] (2) placing the mixture of step (1) in a tubular furnace under a nitrogen atmosphere, heating it to 1200° C. at a rate of 10° C. / min for high temperature treatment for 2 h, and then breaking it up and sieving it after cooling to obtain a graphite negative electrode material.

[0084] Comparative Example 2:

[0085] A method for preparing a graphite negative electrode material comprises the following steps:

[0086] (1) 100 g of natural graphite microspheres with a D50 of 15 μm and 11 g of petroleum asphalt with a softening point of 60° C. were placed in a mixer, the speed was set to 150 r / min, and the mixture was mixed for 90 min to obtain a mixture;

[0087] (2) placing the mixture of step (1) in a hot isostatic press, heating it to 250° C. under a pressure of 100 MPa, maintaining the temperature and pressure for 60 min, and then cooling it to room temperature before breaking it up and screening it;

[0088] (3) The natural graphite obtained in step (2) is placed in a graphitization furnace, treated at 2800° C. for 4 h, and cooled to obtain a natural graphite negative electrode material.

[0089] The physical and chemical properties and electrochemical properties of the graphite materials of the embodiments of the present invention and the comparative examples were tested using the following test methods:

[0090] (1) Use scanning electron microscopy (SEM) to test the sample cross section, such as Figure 1 The figure shows a cross-sectional SEM photograph of the modified natural graphite negative electrode material prepared in Example 1. The internal pores of the particles are greatly reduced, the degree of densification is significantly improved, and at the same time, the surface smoothness is reduced due to the coating of graphene.

[0091] (2) The particle size distribution of the samples was tested using a Malvern laser particle size analyzer.

[0092] (3) Half-cell test method: The graphite materials prepared in the embodiment and the comparative example were mixed uniformly in the ratio of sample: conductive carbon black (SP): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 96.5%: 1%: 1%: 1.5%, coated on a copper foil, and rolled and dried to obtain a negative electrode sheet. The metal lithium sheet was used as the counter electrode. The electrolyte was 1M LiPF6 + EC: DEC: DMC = 1: 1: 1 (volume ratio). The diaphragm was Enjie 25μm PP diaphragm. Button cells were made in a glove box, and battery charge and discharge tests were carried out on the BT2000 equipment of Arbin Company in the United States. The charge and discharge voltage range was 0.005V~2V, and the charge and discharge current was 0.1C. The first discharge capacity and efficiency obtained from the test are shown in Table 1.

[0093] (4) Full battery test method: The graphite material prepared in the embodiment and the comparative example was used as the negative electrode, the 4.4V lithium cobalt oxide material was used as the positive electrode, the 1M LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution was used as the electrolyte, and Enjie ND7M22O was used as the separator to assemble into a 1.5Ah soft-pack full battery. The BT2000 equipment of Arbin Company of the United States was used to carry out charge and discharge cycle test at 25°C in the voltage range of 3 to 4.4V and at a rate of 1C. The cycle performance obtained by the test is shown in Table 1.

[0094] Table 1. Test results of physical and chemical properties and electrochemical properties of graphite materials in Examples and Comparative Examples

[0095]

[0096] As can be seen from Table 1, in Comparative Example 1, only the surface of natural graphite was coated with asphalt, and the internal pores were not filled. The first efficiency was low and the cycle performance was poor; in Comparative Example 2, the internal pores of natural graphite were filled and the surface was coated with asphalt, and no graphene coating was performed. The material cycle performance was good, the first efficiency was also improved, but the specific capacity was low. Comparative Examples 1 to 3 show that increasing the amount of asphalt added to the densified natural graphite can further improve the cycle performance of the material, but the first discharge capacity will decrease due to the increase in asphalt content; Comparative Examples 3 to 5 show that increasing the amount of graphene added can further improve the discharge capacity of the material, but the first efficiency and cycle performance will decrease slightly due to the increase in side reactions. In Examples 1 to 5, natural graphite is filled with internal pores and coated with graphene on the surface at the same time, and the specific capacity of the material is significantly improved, the first efficiency is also high, and the cycle performance is excellent, which solves the problem that it is difficult for natural graphite to have both high capacity and long cycle performance.

[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A graphite negative electrode material, characterized in that: It comprises a densified natural graphite material and a graphene layer coated on the surface of the densified natural graphite material.

2. The graphite negative electrode material according to claim 1, characterized in that The densified natural graphite material is prepared by the following method: 1) mixing natural graphite microspheres with asphalt and then pressurizing and heating them for densification treatment to obtain natural graphite filled with asphalt inside and coated with asphalt on the surface; 2) continuing high-temperature graphitization treatment to obtain the densified natural graphite material.

3. The graphite negative electrode material according to claim 2, characterized in that: Step 1) The mass ratio of natural graphite microspheres to asphalt is 100:(8-20); preferably 100:15; Preferably, the natural graphite microsphere D 50 5 to 25 μm; the graphite negative electrode material D 50 5 to 25 μm; preferably 16.8 to 18 μm; Preferably, the asphalt is any one or more of petroleum asphalt and coal tar asphalt, the softening point of the asphalt is 60-90°C, and the quinoline insoluble content is ≤1%; Preferably, the natural graphite microspheres and the asphalt are mixed in a mixer at a speed of 150 to 300 r / min for 60 to 120 min.

4. The graphite negative electrode material according to claim 2, characterized in that: The specific parameters of the densification treatment by pressurizing and heating in step ·) are: pressurizing pressure of 100-150 MPa, temperature of 250-350° C., and treatment time of 60-120 min.

5. The graphite negative electrode material according to claim 2, characterized in that: In step 2), the graphitization treatment temperature is 2500-3000° C. and the time is 2-10 hours.

6. A method for preparing the graphite negative electrode material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: 1) preparing a densified natural graphite material; 2) adding the densified natural graphite material and a binder into a graphene solution to mix the mixture into a slurry and perform a fusion reaction to obtain a graphene-natural graphite fusion product; and 3) carbonizing the graphene-natural graphite fusion product to obtain a graphite negative electrode material.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the densified natural graphite material, graphene and binder is 100:(5-20):(1-10); preferably 100:(6-8):2; The mass concentration of the graphene solution is (1-5)%; the solvent of the graphene solution is one or a mixture of two or more of water, methanol, ethanol, and N-methylpyrrolidone; The binder is one or a mixture of two or more of sodium hydroxymethyl cellulose, stearic acid, polyvinyl alcohol, phenolic resin, epoxy resin, glucose, starch, and asphalt; The number of graphene layers is 1 to 5, and the diameter of the sheet is 5 to 25 μm.

8. The preparation method according to claim 6, characterized in that: In step 2), the fusion reaction is carried out in a fusion machine at a speed of 50 to 200 r / min for 5 to 30 min; Preferably, step 3) carbonization treatment is carried out in an inert gas at a temperature of 800-1500° C., a heating rate of 5-10° C. / min, and a time of 1-10 h; the inert gas is one or more of nitrogen or argon.

9. A negative electrode, characterized in that It comprises the graphite negative electrode material, negative electrode binder and negative electrode conductive agent as described in any one of claims 1 to 5; preferably, the negative electrode binder is a mixture of sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, and the mass ratio of the two is 1:1.5; preferably, the negative electrode conductive agent is conductive carbon black SP.

10. A lithium ion battery, characterized in that: It comprises the negative electrode, positive electrode, separator and electrolyte as described in claim 9.